THE ANALYSIS OF FUKUGOUDOUSHI ~KAERU AND~KAESU MEANING IN JAPANESE SENTENCES - Andriani, Tasya Ismi (2017)
In the learning of Japanese language, Compound verbs (fukugoudoushi) is one of the important things learned by the learners. This is because the number of verbs in Japanese is quite a lot, but learning resources such as books and others are still limited in number. For the Japanese themselves, fukugoudoushi is not a strange thing and is very familiar in their everyday life. However, foreign learners who are studying Japanese need to have high understanding because fukugoudoushi is one of the hardest aspect. Fukugoudoushi consists of two verbs or more. The meaning which arises from the formation of fukugoudoushi can come from the front element, the rear element, or none at all. Kaeru verb has the meaning of 'to go back' and kaesu verb means 'restore'. However, if those verbs are combined with other verbs and form a compound verb (fukugoudoushi) then its meaning may change or may not change depending on the verb that follows it. This study aims to determine the lexical meaning, the formation of meaning, and the forming words characteristics of fukugoudoushi ~kaeru and ~kaesu. The method used is descriptive analysis that analyzes fukugoudoushi ~kaeru and ~kaesu in Japanese language textbooks, novels, and more. This study describes how the lexical meaning is, then how the formation of fukugoudoushi ~kaeru and ~kaesu is. The results show that some meanings of fukugoudoushi ~kaeru and ~kaesu have dominant front elements (V1) and the other have dominant rear elements (V2). For the forming words characteristics of fukugoudoushi ~kaeru and ~kaesu, they can be seen from classifications verb is in Japanese, Keywords : Fukugoudoushi~kaeru, Fukugoudoushi~kaesu, Lexical Meaning, Verb Classification, Compound Verb, Dalam pembelajaran bahasa Jepang, Fukugoudoushi merupakan salah satu hal yang penting dipelajari oleh pembelajar. Hal tersebut dikarenakan kata kerja di dalam bahasa Jepang cukup banyak, tetapi sumber pembelajaran seperti buku dan yang lainnya masih terbatas jumlahnya. Bagi orang Jepang sendiri, fukugoudoushi sudah tidak asing lagi dan sangat akrab dengan kehidupan sehari-hari. Namun, bagi pembelajar asing yang belajar bahasa Jepang, tentunya perlu pemahaman yang cukup tinggi karena fukugoudoushi merupakan salah satu dari yang tersulit. Kata kerja majemuk (fukugoudoushi) terdiri dari 2 kata kerja atau lebih,. Makna yang ditimbulkan dari pembentukan fukugoudoushi bisa berasal dari unsur depan, unsur belakang ataupun tidak ada sama sekali. Verba kaeru mempunyai arti 'kembali' dan verba kaesu mengandung arti 'mengembalikan'. Namun, jika verba kaeru dan verba kaesu digabungkan dengan verba lainnya dan membentuk verba majemuk (fukugoudoushi) maka maknanya dapat berubah atau pun tidak berubah tergantung dengan verba yang mengikutinya. Penelitian ini bertujuan untuk mengetahui makna leksikal, pembentukan makna, dan karakteristik kata pembentuk dari fukugoudoushi ~kaeru dan ~kaesu. Metode yang digunakan adalah analisis deskriptif yang menganalisis fukugoudoushi ~kaeru dan ~kaesu dalam buku pelajaran bahasa Jepang, novel, dan lainnya. Dalam penelitian ini, menguraikan bagaimana makna leksikal, lalu bagaimana pembentukan makna fukugoudoushi ~kaeru dan ~kaesu. Hasilnya menunjukkan bahwa beberapa makna fukugoudoushi ~kaeru dan kaesu memiliki unsur depan (V1) yang dominan dan yang lainnya memiliki unsur belakang (V2) yang dominan. Untuk karakteristik kata pembentuk fukugoudoushi ~kaeru dan ~kaesu, dilihat dari klasifikasi verba yang ada di dalam bahasa Jepang, Kata kunci : Fukugoudoushi~kaeru, Fukugoudoushi~kaesu, Makna Leksikal, Klasifikasi Verba, Kata Kerja Majemuk,